Radiographic measurement of cardiac size in laboratory mice - Mokhamad Fakhrul Ulum; Deni Noviana (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2018)
This study was to establish quantitative reference range measurements that could be used to support basic data of cardiac size in the laboratory animals. Right and left lateral recumbency (R/L view) and ventral and dorsal recumbency (VD/DV view) radiographs were obtained in 6 normally laboratory mice (Mus musculus). The R/L view heart measurements were the apicobasal length (AB); the maximum width (CD); the distance between the cranial edge of the fifth rib and the caudal edge of the seventh rib (R5-7); the vertical depth of the thorax (H). The VD/DV view cardiac silhouette measurements were maximum length (L); maximum width (W); the width of the thorax (T). In order to determine vertebral heart scale score (VHS), the length and width of the heart were measured and then superimposed to the thoracic vertebrae starting at fourth vertebral (T4) caudally. In order to determine intercostals space (ICS), the CD were measured perpendicularly and superimposed on the intercostals space from fourth costal caudally. The cardiac silhouette was evaluated objectively to describe the cardiac appearance. Lengths of the parameter were determined with a caliper and a ruler in millimeters scale. The result showed that all measurements have not differed significantly between radiographic views (p>0.05).